DETERMINAN PERTUMBUHAN EKONOMI SUMATERA UTARA - Rini Hayati Lubis; Nurul Izzah (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
The economic growth of North Sumatra province in 2019 increased by 5.22 percent compared to the previous year. This increase was caused by several factors, namely investment, labor, government spending, economic growth, inflation and the labor force. Increased government spending will encourage economic growth. Based on data from the Central Statistics Agency that in North Sumatra economic growth continues to increase despite declining government spending. This study aims to examine the factors that influence economic growth. The factors used are investment, labor, government expenditure, unemployment, inflation, and labor force. This sampling method uses saturated sampling technique. The total sample of 30 data for the period 1989 – 2017. Data analysis techniques use a quantitative approach. This study concluded that the variable labor and government expenditure significantly influence economic growth. And investment, unemployment, inflation, and labor force has not effect economic growth. North Sumatra government should increase promotion to attract investors and simplify business licensing administration.